Evektifitas Kredit Usaha Rakyat (KUR) Terhadap Peningkatan UMKM di Kota Dumai - Muhammad Febryan K.; Rosyetti '; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the city dumai since november 2013. This study aims to determine the effectiveness of small loans to the improvement of UMKM in Dumai City, Riau Province. Data used are primary and secondary data. Primary data obtained through interviews, observation and dissemination kuistioner to a population of 1652 with a sample of 43 clients. while the secondary data obtained from the appropriate agencies. methods of data analysis in this study using a non-parametric analysis techniques / free distribution. The analysis is wilcoxom test pairs test and Z test From the analysis we found that, the value of Zcalculate <- Ztable is (-5,713 > -1,96), then H0 is rejected. this shows that financing small loans at PT. Bank BRI branch dumai very effective in supporting the improvement of UMKM in the Dumai City.Keywords : Small Loans (KUR), micro, small and medium businesses (UMKM).